The Analysis of Patient Satisfaction with Services at Genteng Regional Public Hospital - Dian Roshanti; Betty Erda Yoelianita; Wahyu Adri Wirawati; Ivan Rachmawan (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Getting complete health services is a privilege that patients must obtain. Patient satisfaction is a key element that can influence the patient's desire to reuse health services. Therefore, Genteng Regional Public Hospital needs to conduct periodic satisfaction surveys to maintain patient satisfaction periodically. Objectives: This study aims to determine patient satisfaction with services at Genteng Regional Hospital. This study was conducted in September-November 2024. Methods: This research design uses quantitative descriptive. The population in this study was 256 people, with a sample size of 150 people, who were obtained using the Krecjie Morgan table, were selected using a simple random sampling technique, and spread across 43 rooms, polyclinics, and units at the RSUD Genteng Banyuwangi. The variables used are patient satisfaction and service. The questionnaire contains 12 elements: service requirements, service procedures, service time, service schedule, service costs, service type products, indications of negligence, communication competence, service expertise, implementer behavior, handling of complaints, suggestions and input, facilities, and infrastructure with 58 statements. Results: This research consists of 12 elements and each shows the following results: (1)elements of service requirements with a value of 98.375 (Quality Value A); (2) elements of service procedures with a value of 97.611 (Quality Value A); (3) elements of service time with a value of 95.917% (Quality Value A); (4) elements of service schedule suitability with a value of 96.917% (Quality Value A); (5) elements of service costs of 96.861% (Quality Value A); (6) elements of service products of 97.250% (Quality Value A); (7) elements of indications of negligence with a value of 96.833% (Quality Value A); (8) elements of communication competence with a value of 97% (Quality Value A); (9) elements of service expertise with a value of 97% (Quality Value A); (10) elements of implementer behavior with a value of 96.867% (Quality Value A); (11) Complaints, suggestions and input elements with a value of 97.250% (Quality Value A); (12) elements.Conclusions: Based on the research results, the patient satisfaction value for services at Genteng Regional Hospital, Banyuwangi Regency, was 96.911%, which means that patients feel very satisfied and the quality of service is A.